Strategi Kepala Desa Barania Dalam Mencapai Prestasi Sebagai Desa Wisata - Muhammad Amar; Harti Febrianti; Makmur Makmur (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study was to find out how the government of Barania Village achieved achievement as the best Tourism Village in the Cleanliness, Health, Safety, Enverorment Sustainability (CHSE) category. This research uses a descriptive research type with a qualitative approach which is intended to provide a clear description and overall description of the strategy of the head of Barania Village in achieving achievements as a Tourism Village. And using data collection techniques used in this study include observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study show that in implementing the strategy of the head of Barania Village in achieving achievements as a Tourism Village, it can be seen from several indicators, namely, good management of Human Resources (HR), structured allocation of funds, both Village Fund Allocation (ADD) and Allocation Funds Specifically (DAK), the use of technology and information in the Barania Tourism Village cannot be utilized optimally, and the provision of facilities and infrastructure is also inadequate.